Penyelesaian Sengketa Atas Kredit Macet Dalam Perjanjian Kredit Pemilikan Rumah (Studi Kasus Pada PT. Bank Central Asia, Tbk Kantor Cabang Pembantu Boyolali) - Prihatmanto, Gunawan Joko; , Darsono, S.H,M.H (2017)
Credit (KPR) developed many kinds and the demand is increasing. Develop as well as increased demand for program loans (mortgages) can not be separated from the contribution of the parties contained in the mortgage (KPR). In the program mortgage (KPR) there are three parties involved. The parties involved are the consumer as a buyer (debtor), developers (developers) to provide land or house, as well as the creditor banks. Briefly relationship of the parties on the procurement transactions of the house through a mortgage (KPR) is a consumer (debtor) as a buyer, bought the house with the developer (developer) by way of an advance payment (part of the total price of the house) of 30% of the sale price the whole house, while the remaining 70% of consumers borrow / loan through the bank (creditor), by bank loans / consumer credit is then distributed / disbursed to the developer as a settlement house purchase.